2020
DOI: 10.1017/s1460396920000461
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of whole-pelvis radiation therapy of prostate cancers: clinical experience

Abstract: Background: The standard treatment modalities for prostate cancer include surgery, chemotherapy, hormonal therapy and radiation therapy or any combination depending on the stage of the tumour. Radiation therapy is a common and effective treatment modality for low-intermediate-risk patients with localised prostate cancer, to treat the intact prostate and seminal vesicles or prostate bed post prostatectomy. However, for high-risk patients with lymph node involvement, treatment with radiation will usually in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Radiation therapy is a common and effective treatment modality to treat the intact prostate or prostate bed (post-prostatectomy) for low-and intermediate-risk patients with localised prostate cancer or to include the affected lymph nodes for high-risk patients with potential lymph nodes involvement. 4,[56][57][58][59][60][61][62][63] It is also an effective salvage therapy for biochemical recurrence following prostatectomy. Tobacco smoking while receiving radiation therapy is reported to be associated with poor treatment outcomes in prostate cancer patients.…”
Section: Effect Of Tobacco Smoking On Radiotherapy Of Prostate Cancermentioning
confidence: 99%
“…Radiation therapy is a common and effective treatment modality to treat the intact prostate or prostate bed (post-prostatectomy) for low-and intermediate-risk patients with localised prostate cancer or to include the affected lymph nodes for high-risk patients with potential lymph nodes involvement. 4,[56][57][58][59][60][61][62][63] It is also an effective salvage therapy for biochemical recurrence following prostatectomy. Tobacco smoking while receiving radiation therapy is reported to be associated with poor treatment outcomes in prostate cancer patients.…”
Section: Effect Of Tobacco Smoking On Radiotherapy Of Prostate Cancermentioning
confidence: 99%
“…1,2 Although, for distant metastatic diseases, the role of radiotherapy has generally been limited to palliation of symptoms. 1,[3][4][5] According to Yilmaz et al, 5 the radiobiology of radiotherapy hypothesised that the cytotoxic effects of radiation result from direct damage to the deoxyribonucleic acid (DNA) and an indirect generation of cell-damaging free radicals, thus making this treatment modality a local therapy characterised by a high degree of spatial accuracy. However, other investigations [6][7][8][9][10][11][12][13][14][15] have demonstrated that radiotherapy can also induce localised bystander effects, whereby neighbouring unirradiated cells exhibit irradiated effects as a result of signals received from nearby irradiated cells.…”
Section: Introductionmentioning
confidence: 99%